Trade openness and the environmental Kuznets curve: Evidence from cities in the People's Republic of China - Zheng Fang; Bihong Huang; Zhuoxiang Yang (Asian Development Bank Institute (ADBI), 2018)
This paper examines the impact on the environment of economic growth and trade openness in 261 cities in the People's Republic of China (PRC) over the period 2004-2013, using a recently developed, continuously updated, fully modified method that allows for cross-sectional dependence and endogeneity. The study investigates two types of pollutant, industrial wastewater and sulfur dioxide, and employs three measures of openness in the regression. The results show that the environmental Kuznets curve hypothesis holds not only for the whole of the PRC but also for different regions. The paper estimates that wastewater pollution increases with economic development until the per capita gross domestic product (GDP) reaches the turning point of CNY31,849-CNY49,446 (in constant 2002 prices), which varies depending on the specific measure of trade openness. It finds that the turning point for sulfur dioxide occurs at a much lower income level, around CNY9,274-CNY10,103 per capita GDP. Furthermore, the results indicate that cities featuring greater openness tend to have lower industrial wastewater emissions but higher sulfur dioxide emissions.
Keywords: C33; F18; Q42; Q43; 330; environmental Kuznets curve; trade openness; People's Republic of China